Toner and method for producing the same
By using side chain crystalline resin and boric acid in toner, the toner's balance between low-temperature fixation and high-temperature storage stability is solved, achieving high compatibility and excellent performance.
Patent Information
- Application Number
- JP2021134035
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-19
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-08-19
AI Technical Summary
Existing toners are difficult to balance the stability of low-temperature fixation and high-temperature storage, and it is difficult to achieve the dual performance of low-temperature fixation and high-temperature storage.
A resin with side chain crystallinity is used as a binding agent, and the crystallinity of the crystalline resin is improved by adding boric acid to the toner, thereby improving the low-temperature fixation and high-temperature storage stability of the toner.
It realizes high compatibility of toner in low-temperature fixation and high-temperature storage, improving the overall performance of toner.
Smart Images

Figure 0007665473000001 
Figure 0007665473000002 
Figure 0007665473000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a toner (hereinafter sometimes simply referred to as "toner") used in electrophotography, electrostatic recording, and toner jet recording, and a method for producing the toner. [Background technology]
[0002] In recent years, energy saving has been considered as a major technical issue in electrophotographic devices, and a significant reduction in the amount of heat required for fixing devices has been considered. In particular, there is an increasing need for toners that can be fixed with less energy, that is, so-called "low-temperature fixing properties."
[0003] One method for enabling fixation at low temperatures is to lower the glass transition temperature (Tg) of the binder resin in the toner. However, lowering the Tg leads to a decrease in the heat-resistant storage stability of the toner, and it is considered difficult to achieve both low-temperature fixability and heat-resistant storage stability of the toner with this method.
[0004] Therefore, in order to achieve both low-temperature fixability and heat-resistant storage stability of toner, a method of using a resin having crystallinity (hereinafter also referred to as crystalline resin) as a binder resin has been considered. Amorphous resins that are generally used as binder resins for toners do not show a clear endothermic peak in differential scanning calorimeter (DSC) measurements, but crystalline resins have molecular chains arranged regularly, and therefore an endothermic peak (melting point) appears in DSC measurements. Crystalline resins have the property of hardly softening up to the melting point. In addition, crystals melt suddenly at the melting point, which is accompanied by a sudden drop in viscosity. For this reason, crystalline resins have been attracting attention as materials that have excellent sharp melting properties and achieve both low-temperature fixability and heat-resistant storage stability.
[0005] As the crystalline resin for toner, vinyl-based crystalline resin is preferably used. Usually, vinyl-based crystalline resin has a long-chain alkyl group as a side chain in the main chain skeleton, and the long-chain alkyl groups in the side chain crystallize with each other to show crystallinity as a resin. Up to now, improvement of low-temperature fixability and heat-resistant storage stability using vinyl-based crystalline resin has been studied.
[0006] For example, Patent Document 1 proposes a toner that uses a crystalline vinyl resin for the core, which is a copolymer of a polymerizable monomer having a long-chain alkyl group and an amorphous polymerizable monomer, and that is said to achieve both low-temperature fixability and heat-resistant storage stability. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2014-130243 A Summary of the Invention [Problem to be solved by the invention]
[0008] The toner described in Patent Document 1 uses a binder resin in which a polymerizable monomer having a long-chain alkyl group and an amorphous polymerizable monomer are copolymerized. These resins show good low-temperature fixing properties. However, the inventors' studies have revealed that a binder resin in which a polymerizable monomer having a long-chain alkyl group and an amorphous polymerizable monomer are copolymerized may not provide sufficient crystallinity, and there is room for improvement in terms of storage stability in a high-temperature environment. The present disclosure provides a toner that can achieve both low-temperature fixability and high-temperature storage stability at a high level, and a method for producing the toner. [Means for solving the problem]
[0009] The present disclosure relates to a toner having toner particles containing a binder resin, the binder resin has a side-chain crystalline polymer B having a monomer unit A formed of at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms; The toner particles relate to a toner containing boric acid.
[0010] The present disclosure also provides a method for producing a toner having toner particles containing a binder resin, comprising: The method for producing the toner comprises the following steps (1) to (3): (1) A monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms. A dispersion of resin particles having the binder resin containing at least a side chain crystalline polymer B having the side chain crystalline polymer B is prepared. Manufacturing A dispersion step of (2) an aggregation step of mixing at least the dispersion of the resin fine particles and aggregating the mixture to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having The toner production method relates to a toner production method in which boric acid is present in the dispersion liquid in at least any one of the steps (1) to (3).
[0011] The present disclosure also provides a method for producing a toner having toner particles containing a binder resin, comprising: The method for producing the toner comprises the following steps (1) to (3): (1) A dispersion of resin particles having the binder resin containing at least a side-chain crystalline polymer B having a monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms is prepared. Manufacturing A dispersion step of (2) an aggregation step of mixing at least the dispersion of the resin fine particles and aggregating the mixture to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having The toner production method relates to a toner production method in which borax is added to the dispersion liquid in at least any one of the steps (1) to (3). Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a toner that can achieve both high levels of low-temperature fixability and high-temperature storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. (Meth)acrylic acid ester means acrylic acid ester and / or methacrylic acid ester. "Monomer unit" means the reacted form of a monomer substance in a polymer. For example, one section of carbon-carbon bond in the main chain of a polymer in which vinyl monomers are polymerized is considered to be one unit. A vinyl monomer can be represented by the following formula (Z). [ka] [In formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), R Z2 represents an optional substituent. The crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.
[0014] The present disclosure relates to a toner having toner particles containing a binder resin, the binder resin has a side-chain crystalline polymer B having a monomer unit A formed of at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms; The toner particles relate to a toner containing boric acid.
[0015] As described above, in order to achieve both low-temperature fixability and heat-resistant storage stability of a toner, a method of using a resin having crystallinity as a binder resin has been considered, and a side-chain crystalline resin is preferably used as the crystalline resin. A side-chain crystalline resin is a resin having a long-chain alkyl group on a side chain relative to the skeleton (main chain) of an organic structure, and has a structure capable of forming a crystalline structure between the side chains.
[0016] While main-chain crystalline resins, such as crystalline polyesters, crystallize by folding the main chain, side-chain crystalline resins are thought to crystallize between the side chains of a single molecule. Therefore, they can crystallize even in a very narrow area, and are less susceptible to a decrease in crystallinity due to the surrounding environment compared to main-chain crystalline resins. Therefore, by using a side-chain crystalline resin as the binder resin, it is thought that a toner having superior sharp melt properties and achieving both low-temperature fixability and heat-resistant storage stability can be obtained.
[0017] As such a side chain crystalline resin, a vinyl-based crystalline resin is preferably used. In the present disclosure, from the viewpoint of controlling the melting point and crystallinity, a side chain crystalline polymer B having a monomer unit A formed of at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms is used.
[0018] However, even if a side-chain crystalline resin is used, when it is subjected to various temperature histories during the toner manufacturing process, the half-width of the peak corresponding to the crystalline component in a differential scanning calorimeter (DSC) increases, the crystalline component becomes broad, and the melting point tends to decrease. If crystallization is insufficient, the storage stability of the toner in a high-temperature environment tends to decrease.
[0019] In order to solve these problems, the present inventors have investigated the toner configuration required for achieving both low-temperature fixing ability and high-temperature storage stability in a toner using a side-chain crystalline resin, and have found that the crystallinity of the side-chain crystalline resin is improved and the above problems can be solved by adding boric acid to toner particles using a binder resin having the above-mentioned side-chain crystalline polymer B.
[0020] The reason why the addition of boric acid improves crystallinity is thought to be as follows. Boric acid is expressed as B(OH)3 and has a hydroxyl group. When boric acid is used in a side-chain crystalline resin, it is expected that the hydroxyl group of the boric acid and the ester bond of the (meth)acrylic acid ester present in the monomer unit A part of the crystalline resin will interact loosely. As a result, It is believed that the orientation of the long-chain alkyl portion of the monomer unit A is promoted via the acid, the crystallinity of the side-chain crystalline portion is improved, and both low-temperature fixability and storage stability can be achieved at a high level.
[0021] These effects can be obtained only by making the binder resin having the side-chain crystalline polymer B and boric acid coexist, and are difficult to obtain with other crystalline resins. Boric acid may be present in the toner particles in the form of unsubstituted boric acid, and may be used in the form of organic boric acid, borate salt, borate ester, etc., at the stage of use as a raw material.
[0022] When the toner is produced in an aqueous medium, it is preferable to add it as a borate from the viewpoint of reactivity and production stability, and specific examples thereof include sodium tetraborate, ammonium borate, etc., and borax is particularly preferably used. Borax is expressed as a decahydrate of sodium tetraborate Na2B4O7, and changes to boric acid in an acidic aqueous solution, so borax is preferably used when the toner is used in an acidic environment in an aqueous medium.
[0023] The content of boric acid in the toner is preferably 0.1% by mass or more and 10.0% by mass or less. When the content is 0.1% by mass or more, the effect of promoting crystallinity is easily obtained, and when the content is 10.0% by mass or less, sharp melt performance is improved due to appropriate crosslinking. The content of boric acid in the toner is preferably 0.5% by mass or more and 8.0% by mass or less, more preferably 0.8% by mass or more and 6.0% by mass or less.
[0024] The content of the side chain crystalline polymer B in the binder resin is preferably 50.0% by mass or more, more preferably 70.0% by mass or more, and even more preferably 80.0% by mass or more. By making the content 50.0% by mass or more, the sharp melting property of the toner is easily maintained, and the low temperature fixing property is further improved. The upper limit is not particularly limited, but is preferably 100.0% by mass or less.
[0025] The binder resin may contain other resins in addition to the side chain crystalline polymer B. Examples of resins that can be used as the binder resin other than the polymer B include known vinyl resins, polyester resins, polyurethane resins, and epoxy resins. Among these, vinyl resins, polyester resins, and polyurethane resins are preferred from the viewpoint of electrophotographic properties.
[0026] The side chain crystalline polymer B preferably has a monomer unit A made of a polymerizable monomer A and a monomer unit C made of a polymerizable monomer C different from the polymerizable monomer A. By copolymerizing the polymerizable monomer C together with the polymerizable monomer A, it is possible to reduce the content of alkyl groups to a certain level or more, and the elasticity at around room temperature can be further improved, thereby further improving durability.
[0027] In addition, the SP value of monomer unit A is SP 11 (J / cm 3 ) 0.5 The SP value of the monomer unit C is SP 21 (J / cm 3 ) 0.5 When the SP value of the polymerizable monomer A is SP 12(J / cm 3 ) 0.5 The SP value of the polymerizable monomer C is SP 22 (J / cm 3 ) 0.5 When set at , the following formula (2) is preferably satisfied. 2.00≦(SP 21 -SP 11 )≦25.00 ···(1) 0.50≦(SP 22 -SP 12 )≦15.00 (2)
[0028] Here, the SP value is an abbreviation for solubility parameter, and is a value that serves as an index of solubility. The calculation method will be described later. The unit of the SP value is (J / m 3 ) 0.5 However, 1 (cal / cm 3 ) 0.5 =2.045×10 3 (J / m 3 ) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of
[0029] By satisfying the above formula (1) or formula (2), even if the polymerizable monomer A and the polymerizable monomer C are used in combination in the side chain crystalline polymer B, the crystallinity is not reduced and the melting point is easily maintained. This makes it easier to achieve a high degree of compatibility between low temperature fixability and durability. The mechanism behind this is presumed to be as follows.
[0030] Monomer unit A is incorporated into side-chain crystalline polymer B (hereinafter also referred to as "polymer B"), and the monomer units A aggregate to exhibit crystallinity. Normally, if other monomer units are incorporated here, this inhibits crystallization, making it difficult for the polymer to exhibit crystallinity. This tendency becomes more pronounced when monomer unit A and other monomer units are randomly bonded within one molecule of the polymer.
[0031] On the other hand, S.P. 22 -SP12 By using a polymerizable monomer in which the ratio is within the range of the above formula (2), it is believed that the polymerizable monomer A and the polymerizable monomer C can be bonded to a certain degree of continuity during polymerization, rather than being bonded randomly. As a result, the monomer units A in the polymer B can be aggregated together, and it is believed that the crystallinity can be increased even if other monomer units are incorporated, and the melting point can be maintained. In other words, it is preferable that the polymer B has a crystalline portion containing the monomer unit A derived from the polymerizable monomer A. In addition, it is preferable that the polymer B has an amorphous portion containing the monomer unit C derived from the polymerizable monomer C.
[0032] Also, SP 21 -SP 11 is within the range of the above formula (1), it is considered that the monomer unit A and the monomer unit C in the polymer B can form a clearly phase-separated state without being miscible with each other, and the melting point can be maintained without decreasing the crystallinity.
[0033] SP 22 -SP 12 When SP is 0.50 or more, the melting point of the polymer B falls within a suitable range, and the heat-resistant storage stability is further improved. 22 -SP 12 When SP is 15.00 or less, the copolymerizability of the polymer B is good, and the low-temperature fixability is further improved. 22 -SP 12 The lower limit is more preferably 0.60 or more, even more preferably 2.00 or more, and even more preferably 3.00 or more, and the upper limit is more preferably 10.00 or less, and even more preferably 7.00 or less.
[0034] Similarly, S.P. 21 -SP 11 When SP is 2.00 or more, the melting point of the polymer B falls within a suitable range, and the heat-resistant storage stability is further improved. 21 -SP 11 When SP is 25.00 or less, the copolymerizability of the polymer B is good, and the low-temperature fixability is further improved. 21-SP 11 The lower limit is more preferably 3.00 or more, even more preferably 4.00 or more, and even more preferably 5.00 or more, and the upper limit is more preferably 20.00 or less, and even more preferably 15.00 or less.
[0035] In addition, when multiple types of monomer units satisfying the requirements of the monomer unit A are present in the polymer B, SP 11 The value of is the weighted average of the SP values of each monomer unit. For example, if the SP value is SP 111 Monomer unit A 1 Based on the total number of moles of monomer units that satisfy the requirements of monomer unit A, 1 Contains mol% and SP value is SP 112 Monomer unit A 2 Based on the number of moles of all monomer units that satisfy the requirements of monomer unit A (100-A 1 ) mole percent SP value (SP 11 )teeth, SP 11 =(SP 111 ×A 1 +SP 112 ×(100-A 1 )) / 100 The calculation is the same when three or more monomer units that satisfy the requirements of monomer unit A are included. 12 Similarly, represents an average value calculated from the molar ratio of each polymerizable monomer A.
[0036] Regarding the monomer unit C by the polymerizable monomer C, if there is one type of monomer unit C, the relationship of formulas (1) and (2) is calculated for the monomer unit C and the polymerizable monomer C. If there are multiple types of monomer unit C, the relationship of formulas (1) and (2) is calculated for each monomer unit C and polymerizable monomer C.
[0037] The content of monomer unit A in polymer B is preferably 5.0 mol % to 79.0 mol %, more preferably 10.0 mol % to 60.0 mol %, and even more preferably 20.0 mol % to 40.0 mol %, based on the total number of moles of all monomer units in polymer B. The content of the monomer unit A in the polymer B is preferably from 15.0% by mass to 90.0% by mass, more preferably from 35.0% by mass to 80.0% by mass, and further preferably from 50.0% by mass to 70.0% by mass.
[0038] The content of the polymerizable monomer A in the polymerizable monomer composition for producing the polymer B is preferably 5.0 mol % to 79.0 mol %, more preferably 10.0 mol % to 60.0 mol %, and even more preferably 20.0 mol % to 40.0 mol %, based on the total number of moles of all polymerizable monomers in the composition. Furthermore, the content of the polymerizable monomer A in the polymerizable monomer composition for producing the polymer B is preferably 15.0 mass% to 90.0 mass%, more preferably 35.0 mass% to 80.0 mass%, and even more preferably 50.0 mass% to 70.0 mass%.
[0039] The content of monomer unit C in polymer B is preferably 20.0 mol % to 94.0 mol %, more preferably 40.0 mol % to 85.0 mol %, and even more preferably 40.0 mol % to 70.0 mol %, based on the total number of moles of all monomer units in polymer B. The content of monomer unit C in polymer B is preferably 8.0% by mass to 75.0% by mass, more preferably 15.0% by mass to 55.0% by mass, and further preferably 20.0% by mass to 40.0% by mass.
[0040] The content of the polymerizable monomer C in the polymerizable monomer composition for producing the polymer B is preferably 20.0 mol % to 94.0 mol %, more preferably 40.0 mol % to 85.0 mol %, and even more preferably 40.0 mol % to 70.0 mol %, based on the total number of moles of all polymerizable monomers in the composition. Furthermore, the content of the polymerizable monomer C in the polymerizable monomer composition for producing the polymer B is preferably 8.0 mass% to 75.0 mass%, more preferably 15.0 mass% to 55.0 mass%, and even more preferably 20.0 mass% to 40.0 mass%.
[0041] When the content of the monomer unit A in the polymer B and the content of the polymerizable monomer A in the polymerizable monomer composition are within the above ranges, the polymer B exhibits sharp melting properties and retains elasticity at around room temperature, resulting in a toner with superior low-temperature fixing properties and durability. When the content of each of the monomer unit A and the polymerizable monomer A is 5.0 mol % or more, the amount of crystallization of the polymer B is large, the sharp melting property is improved, and the low-temperature fixing property is further improved. On the other hand, when the content of each of the monomer unit A and the polymerizable monomer A is 80.0 mol % or less, the elasticity at around room temperature is sufficient, and the durability of the toner is further improved.
[0042] When the content of the monomer unit C in the polymer B and the content of the polymerizable monomer C in the polymerizable monomer composition are within the above ranges, the polymer B can improve its elasticity at around room temperature while maintaining sharp melting properties. As a result, the toner has excellent low-temperature fixing properties and durability. In addition, the crystallization of the monomer unit A in the polymer B is less likely to be hindered, and the melting point can be easily maintained. When the content ratio of each of the monomer unit C and the polymerizable monomer C is 20.0 mol % or more, the elasticity of the polymer B is sufficient, and the durability of the toner is improved. On the other hand, when the content ratio is 95.0 mol % or less, the sharp melting property of the polymer B is improved, and the low-temperature fixing property is improved.
[0043] When polymer B contains monomer units A derived from two or more kinds of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms, the content ratio of monomer units A represents the total molar ratio or mass ratio thereof. Similarly, when the polymerizable monomer composition used for polymer B contains two or more kinds of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms, the content ratio of polymerizable monomer A represents the total molar ratio or mass ratio thereof.
[0044] In addition, when two or more kinds of monomer units C derived from polymerizable monomer C satisfying formula (1) are present in polymer B, the ratio of monomer units C represents the total molar ratio or mass ratio thereof. Similarly, in the case where the polymerizable monomer composition used in polymer B contains two or more kinds of polymerizable monomer C, the content ratio of polymerizable monomer C represents the total molar ratio or mass ratio thereof.
[0045] The polymer B preferably has a monomer unit A having a structure represented by the following formula (I). The polymer B has a crystalline portion derived from a long-chain alkyl group present in the monomer unit A. The monomer unit A (or C) is, for example, a monomer unit obtained by addition polymerization (vinyl polymerization) of a polymerizable monomer A (or C). [ka]
[0046] [In formula (I), R Z1 represents a hydrogen atom or a methyl group, and R represents an alkyl group having 18 to 36 carbon atoms (preferably a linear alkyl group having 18 to 30 carbon atoms).]
[0047] The polymerizable monomer A is at least one selected from the group consisting of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms. Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dodricontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].
[0048] Among these, from the viewpoint of storage stability of the toner, preferably, it is at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms. More preferably, it is at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 30 carbon atoms. Even more preferably, it is at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate, and even more preferably, it is at least one selected from the group consisting of linear behenyl (meth)acrylate. The polymerizable monomer A may be used alone or in combination of two or more kinds.
[0049] As the polymerizable monomer C that forms the monomer unit C, for example, among the polymerizable monomers listed below, a polymerizable monomer that satisfies the formula (2) can be used. The polymerizable monomer C may be used alone or in combination of two or more kinds. Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (such as acrylic acid and methacrylic acid) having an ethylenically unsaturated bond by a known method.
[0050] Monomers having a urethane group: For example, alcohols having 2 to 22 carbon atoms having an ethylenically unsaturated bond (e.g., 2-hydroxyethyl methacrylate, vinyl alcohol, etc.) and isocyanates having 1 to 30 carbon atoms [monoisocyanate compounds (benzenesulfonyl isocyanate, tosyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, t-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, , 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, and 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate and 2,4,4-trimethylhexamethylene diisocyanate, etc.), alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, etc.), and aromatic A monomer obtained by reacting an aromatic diisocyanate compound (such as phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate) by a known method, and Alcohols with 1 to 26 carbon atoms (methanol, ethanol, propanol, isopropyl alcohol, butanol, t-butyl alcohol, pentanol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, undecyl alcohol, lauryl alcohol, dodecyl alcohol, myristyl alcohol, pentadecyl alcohol, cetanol, heptadecanol, stearyl alcohol, isostearyl alcohol, elaidyl alcohol, oleyl alcohol, linoleyl alcohol, linolenyl alcohol, nonadecyl alcohol, heneicosanol, behenyl alcohol, erucyl alcohol, etc.) and isocyanates with 2 to 30 carbon atoms having ethylenic unsaturated bonds [2 - Monomers obtained by reacting isocyanatoethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, etc., by a known method.
[0051] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (such as normal butylamine, t-butylamine, propylamine, and isopropylamine), secondary amine (such as di-normal ethylamine, di-normal propylamine, and di-normal butylamine), aniline, and cycloxylamine] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate, etc.
[0052] Among them, it is preferable to use a monomer having a nitrile group, an amide group, a urethane group, a hydroxy group, or a urea group.More preferably, the polymerizable monomer C is a monomer having at least one functional group selected from the group consisting of a nitrile group, an amide group, a hydroxy group, a urethane group, and a urea group, and an ethylenically unsaturated bond. By having these, the melting point of the polymer B is likely to be high, and the heat-resistant storage stability is likely to be improved. In addition, the elasticity around room temperature is increased, and the durability is likely to be improved.
[0053] As the polymerizable monomer C, vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate are also preferably used. Vinyl esters are non-conjugated monomers and tend to maintain a moderate reactivity with the polymerizable monomer A. This is thought to facilitate the formation of a state in which monomer units derived from the polymerizable monomer A are aggregated and bonded in the polymer B, increasing the crystallinity of the polymer B and making it easier to achieve both low-temperature fixability and heat-resistant storage stability.
[0054] The polymerizable monomer C preferably has an ethylenically unsaturated bond, and more preferably has one ethylenically unsaturated bond. The polymerizable monomer C is preferably at least one selected from the group consisting of the following formulae (A) and (B). [ka]
[0055] In formula (A), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 1 teeth, -C≡N, -C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. vinegar.), Hydroxy groups, -COOR 11 (R 11 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4), or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), -NHCOOR12 (R 12 represents an alkyl group having 1 to 4 carbon atoms. -NH-C(=O)-N(R 13 )2(Two R 13 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms), -COO(CH2)2NHCOOR 14 (R 14 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH2)2-NH-C(=O)-N(R 15 )2(Two R 15 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 2 represents a hydrogen atom or a methyl group. In formula (B), R 3 represents an alkyl group having 1 to 4 carbon atoms, R 4 represents a hydrogen atom or a methyl group.
[0056] The polymerizable monomer C is preferably at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and methyl methacrylate, and more preferably at least one selected from the group consisting of acrylonitrile and methacrylonitrile.
[0057] The polymer B is preferably a vinyl polymer. Examples of the vinyl polymer include polymers of monomers containing ethylenically unsaturated bonds. The ethylenically unsaturated bond refers to a carbon-carbon double bond capable of radical polymerization, and examples of the ethylenically unsaturated bond include a vinyl group, a propenyl group, an acryloyl group, and a methacryloyl group.
[0058] The monomer unit C is preferably at least one selected from the group consisting of a monomer unit represented by the following formula (II) and a monomer unit represented by the following formula (III). [ka]
[0059] (In formula (II), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 1 teeth, -C≡N, -C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Hydroxy groups, -COOR 11 (R 11 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4), or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), -NHCOOR 12 (R 12 represents an alkyl group having 1 to 4 carbon atoms; -NH-C(=O)-N(R 13 )2(Two R 13 are each independently a hydrogen atom or It represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms). -COO(CH2)2NHCOOR 14 (R 14 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH2)2-NH-C(=O)-N(R 15 )2(Two R 15 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 2 represents a hydrogen atom or a methyl group. (In formula (III), R 3 represents an alkyl group having 1 to 4 carbon atoms, R 4 represents a hydrogen atom or a methyl group.
[0060] The polymer B may contain, in addition to the monomer unit A made from the polymerizable monomer A and the monomer unit C made from the polymerizable monomer C described above, a monomer unit D made from a polymerizable monomer D different from the polymerizable monomer A and the polymerizable monomer C.
[0061] In addition, the polymerizable monomer composition for forming the polymer B may contain, in addition to the polymerizable monomer A and the polymerizable monomer C, a polymerizable monomer D different from the polymerizable monomer A and the polymerizable monomer C.
[0062] As the polymerizable monomer D, among the monomers listed in the section on the polymerizable monomer C, a monomer not satisfying formula (2) can be used. In addition, the following monomers which do not have the above-mentioned nitrile group, amide group, urethane group, hydroxy group, urea group, or carboxy group can also be used. For example, styrene and its derivatives such as styrene and o-methylstyrene, and (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. As the polymerizable monomer D, styrene is preferred from the viewpoint of copolymerizability with other monomers.
[0063] The content of monomer unit D in polymer B is preferably 1.0 mol % to 25.0 mol %, and more preferably 10.0 mol % to 20.0 mol %, based on the total number of moles of all monomer units in polymer B. The content of monomer unit D in polymer B is preferably from 1.0% by mass to 20.0% by mass, and more preferably from 5.0% by mass to 15.0% by mass.
[0064] Furthermore, the weight average molecular weight (Mw) of the tetrahydrofuran (THF) soluble portion of polymer B measured by gel permeation chromatography (GPC) is preferably 10,000 to 200,000, and more preferably 20,000 to 150,000. When the weight average molecular weight (Mw) is within the above range, elasticity at around room temperature is easily maintained.
[0065] The melting point of the polymer B is preferably 50° C. to 80° C., more preferably 53° C. to 70° C. When the melting point is within the above range, the low-temperature fixability and heat-resistant storage stability are further improved. The melting point of the polymer B can be adjusted by the type and amount of the polymerizable monomer used, the amount of boric acid added, etc. The half-value width of the peak corresponding to polymer B measured by a differential scanning calorimeter of the toner is preferably 2.00° C. or less, and more preferably 1.85° C. or less. Since a lower half-value width indicates higher crystallinity, the lower limit is not particularly limited, but is preferably 0.50° C. or more, for example.
[0066] <Resins other than polymer B> The binder resin may contain a resin other than the polymer B, if necessary. Examples of the resin other than the polymer B used in the above include the following resins.
[0067] Examples of the copolymer include homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; and polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyester resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins. Among these, styrene copolymers and polyester resins are preferred, and polyester resins are more preferred. Furthermore, it is preferred that resins other than polymer B are amorphous.
[0068] The polyester resin is preferably a condensation polymer of a carboxylic acid component and an alcohol component. Examples of the divalent carboxylic acid component constituting the polyester moiety include the following dicarboxylic acids or derivatives thereof. Benzenedicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, or their anhydrides or lower alkyl esters; alkyldicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or their anhydrides or lower alkyl esters; alkenylsuccinic acids or alkylsuccinic acids having an average carbon number of 1 to 50, or their anhydrides or lower alkyl esters; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid, or their anhydrides or lower alkyl esters.
[0069] On the other hand, examples of the dihydric alcohol component constituting the polyester moiety include the following. Ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, 1,4-cyclohexanedimethanol (CHDM), hydrogenated bisphenol A, bisphenol and its derivatives represented by formula (I-1): and diols represented by formula (I-2). [ka]
[0070] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.) [ka]
[0071] (In the formula, R' is an ethylene or propylene group, and x' and y' are each an integer of 0 or more. and the average of x'+y' is between 0 and 10.
[0072] The components constituting the polyester segment may contain, in addition to the above-mentioned divalent carboxylic acid component and divalent alcohol component, a trivalent or higher carboxylic acid component and a trivalent or higher alcohol component. The trivalent or higher carboxylic acid component is not particularly limited, but examples thereof include trimellitic acid, trimellitic anhydride, pyromellitic acid, etc. Furthermore, the trivalent or higher alcohol component includes trimethylolpropane, pentaerythritol, glycerin, etc.
[0073] <Release agent> The toner particles may contain a wax as a release agent. Examples of the wax include the following. Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene Saturated fatty acid bisamides such as bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty acid metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0074] Among these waxes, from the viewpoint of improving low-temperature fixing property and fixing separation property, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax. Hydrocarbon waxes are more preferred from the viewpoint of further improving hot offset resistance. The content of the wax is preferably 3 to 8 parts by mass per 100 parts by mass of the binder resin.
[0075] Furthermore, in an endothermic curve during temperature rise measured by a differential scanning calorimetry (DSC) device, the peak temperature of the maximum endothermic peak of the wax is preferably 45° C. to 140° C. When the peak temperature of the maximum endothermic peak of the wax is within the above range, the toner can have both good storage stability and good hot offset resistance.
[0076] <Coloring agent> The toner particles may contain a colorant. The colorant may be any of the following: a black colorant, carbon black; a yellow colorant, a magenta colorant, and a cyan colorant. Examples of the colorant include those toned to black using a coloring agent. As the colorant, a pigment may be used alone, or a dye and a pigment may be used in combination. From the viewpoint of image quality of a full-color image, it is preferable to use a dye and a pigment in combination.
[0077] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0078] Examples of pigments for cyan toners include: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments with 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Examples of dyes for cyan toners include CI Solvent Blue 70.
[0079] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.
[0080] These colorants can be used alone or in mixture, or in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner. The content of the colorant is preferably 0.1 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.
[0081] <Charge control agent> The toner particles may contain a charge control agent as necessary. By blending a charge control agent, the charge characteristics can be stabilized, and the amount of triboelectric charge can be optimally controlled according to the development system. As the charge control agent, a known one can be used, but in particular, a metal compound of an aromatic carboxylic acid is preferred, which is colorless, has a high charging speed of the toner, and can stably maintain a constant amount of charge.
[0082] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonic acid ester on the side chain, polymeric compounds having carboxylate or carboxylate on the side chain, boron compounds, urea compounds, and silicon compounds. , and calixarenes. The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, and more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.
[0083] <Toner manufacturing method> The method for producing the toner is not particularly limited, and known methods such as a pulverization method, a suspension polymerization method, a solution suspension method, an emulsion aggregation method, and a dispersion polymerization method can be used. In any of these methods for producing toner particles, it is preferable to obtain toner particles by adding a boric acid source when mixing raw materials. Here, the toner is preferably produced by the method shown below. That is, the toner is preferably produced by an emulsion aggregation method.
[0084] Preferably, the method for producing a toner having toner particles containing a binder resin comprises the following steps (1) to (3): (1) A dispersion of resin particles having a binder resin containing at least a side-chain crystalline polymer B having a monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms is prepared. ManufacturingA dispersion step of (2) an aggregation step of mixing at least the dispersion of the resin fine particles and aggregating the mixture to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having In any one of steps (1) to (3), boric acid is present in the dispersion or the aggregates. More preferably, boric acid is present in the dispersion or the aggregates in step (1) or (2). Still more preferably, boric acid is present in the dispersion during mixing in step (2). When the toner is produced by the emulsion aggregation method, boric acid is likely to be uniformly dispersed in the side chain crystalline polymer B, and crystallization is likely to be uniformly promoted throughout the entire toner particle.
[0085] Also, preferably, a method for producing a toner having toner particles containing a binder resin includes the following steps (1) to (3): (1) A dispersion of resin particles having a binder resin containing at least a side-chain crystalline polymer B having a monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms is prepared. Manufacturing A dispersion step of (2) an aggregation step of mixing at least the dispersion of the resin fine particles and aggregating the mixture to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having It is preferable to add borax to the dispersion or the aggregates in at least one of steps (1) to (3). More preferably, borax is added to the dispersion or the aggregates in step (1) or (2). Still more preferably, borax is added to the dispersion during mixing of the dispersion before aggregation in step (2). The emulsion aggregation method will be described in detail below.
[0086] <Emulsification aggregation method> The emulsion aggregation method is a method in which an aqueous dispersion of fine particles made of the constituent materials of toner particles, which are sufficiently small relative to the target particle size, is prepared in advance, and the fine particles are aggregated in an aqueous medium until they reach the particle size of the toner particles, and the resin is fused by heating or the like to produce toner particles. That is, in the emulsion aggregation method, a dispersion process is performed to prepare a dispersion liquid of fine particles made of the constituent materials of the toner particles, and a process is performed to aggregate the fine particles made of the constituent materials of the toner particles to obtain a particle diameter of the toner particles. Toner particles are manufactured through a process that involves controlling the particle size until the particle size reaches a certain level, a fusion process in which the resin contained in the resulting aggregated particles is fused together, a subsequent cooling process, a metal removal process in which the resulting toner is filtered and excess polyvalent metal ions are removed, a filtration and washing process in which the toner is washed with ion-exchanged water or the like, and a process in which the washed toner particles are dehydrated and dried.
[0087] <Step of preparing a resin particle dispersion (dispersion step)> The resin microparticle dispersion liquid can be prepared by a known method, but is not limited to these methods.The known methods include, for example, emulsion polymerization method, self-emulsification method, phase inversion emulsification method in which resin is emulsified by adding aqueous medium to the resin solution dissolved in organic solvent, and forced emulsification method in which resin is forcedly emulsified by high temperature treatment in aqueous medium without using organic solvent. Specifically, the binder resin is dissolved in an organic solvent capable of dissolving it, and a surfactant or a basic compound is added. In this case, if the binder resin is a crystalline resin having a melting point, it may be dissolved by heating it to above its melting point. Then, while stirring with a homogenizer or the like, an aqueous medium is slowly added to precipitate the resin fine particles. Thereafter, the solvent is removed by heating or reducing pressure to prepare an aqueous dispersion of the resin fine particles. Any organic solvent can be used to dissolve the resin as long as it can dissolve the resin, but it is preferable to use an organic solvent that forms a homogeneous phase with water, such as toluene, from the viewpoint of suppressing the generation of coarse powder.
[0088] The surfactant used in the emulsification is not particularly limited, but examples thereof include anionic surfactants such as sulfate salts, sulfonate salts, carboxylate salts, phosphate esters, and soap salts; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more. Examples of the basic compound used in the dispersion step include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol. The basic compound may be used alone or in combination of two or more. The volume-based 50% particle diameter (D50) of the binder resin particles in the aqueous dispersion of the resin particles is preferably 0.05 μm to 1.0 μm, and more preferably 0.05 μm to 0.4 μm. By adjusting the volume-based 50% particle diameter (D50) to the above range, it becomes easy to obtain toner particles with a volume average particle diameter of 3 μm to 10 μm, which is appropriate for toner particles. The volume-based 50% particle size (D50) is measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso).
[0089] <Colorant particle dispersion> The colorant particle dispersion liquid used as required can be prepared by the known methods described below, but is not limited to these methods. The colorant, the aqueous medium, and the dispersant can be mixed by a known mixer such as a stirrer, an emulsifier, or a disperser. The dispersant used here can be a known one such as a surfactant or a polymer dispersant. Although both the surfactant and the polymer dispersant can be removed in the washing step described below, the surfactant is preferred from the viewpoint of washing efficiency. Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soap-based surfactants; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, nonionic surfactants or anionic surfactants are preferred. A nonionic surfactant and an anionic surfactant may be used in combination. The surfactant may be used alone or in combination of two or more. The concentration of the surfactant in the aqueous medium is preferably 0.5% by mass to 5% by mass.
[0090] The content of the colorant particles in the colorant particle dispersion is not particularly limited, but is preferably 1% by mass to 30% by mass with respect to the total mass of the colorant particle dispersion. From the viewpoint of dispersibility of the colorant in the toner finally obtained, the dispersed particle size of the colorant particles in the aqueous dispersion of the colorant is preferably 50% particle size (D50) based on volume of 0.5 μm or less. For the same reason, the dispersed particle size of the colorant particles in the aqueous medium is preferably 90% particle size (D90) based on volume of 2 μm or less. The dispersed particle size of the colorant particles dispersed in the aqueous medium is measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150: manufactured by Nikkiso). Known mixers such as stirrers, emulsifiers, and dispersers used when dispersing a colorant in an aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills, and paint shakers. These may be used alone or in combination.
[0091] <Release agent (aliphatic hydrocarbon compound) fine particle dispersion> If necessary, a dispersion of releasing agent particles may be used. The dispersion of releasing agent particles can be prepared by the following known methods, but is not limited to these methods. A release agent microparticle dispersion can be produced by adding the release agent to an aqueous medium containing a surfactant, heating the mixture to above the melting point of the release agent, dispersing the mixture into particles using a homogenizer with strong shearing capabilities (e.g., M Technique's "Clearmix W Motion") or a pressure discharge type disperser (e.g., Golin Homogenizer) and then cooling the mixture below the melting point. The particle size of the dispersion of the release agent particles in the aqueous dispersion of the release agent is preferably 50% particle size (D50) based on volume of 0.03 μm to 1.0 μm, more preferably 0.1 μm to 0.5 μm. It is also preferable that no coarse particles of 1 μm or more exist. By setting the particle size of the release agent fine particle dispersion within the above range, the release agent can be finely dispersed in the toner, the exudation effect during fixing can be maximized, and good separation properties can be obtained. The particle size of the release agent fine particle dispersion dispersed in the aqueous medium can be measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150: manufactured by Nikkiso).
[0092] <Mixing process> In the mixing step, a mixture is prepared by mixing the resin fine particle dispersion and, if necessary, at least one of the release agent fine particle dispersion and the colorant fine particle dispersion, using a known mixing device such as a homogenizer or a mixer.
[0093] <Step of forming aggregate particles (aggregation step)> In the aggregating step, the fine particles contained in the mixed liquid prepared in the mixing step are aggregated to form aggregates having a desired particle size. At this time, an aggregating agent is added and mixed, and at least one of heating and mechanical power is appropriately applied as necessary to form aggregates in which the resin fine particles and at least one of the release agent fine particles and the colorant fine particles are aggregated as necessary.
[0094] Examples of the flocculant include organic flocculants such as cationic surfactants of quaternary salts and polyethyleneimine; inorganic metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, and calcium nitrate; inorganic ammonium salts such as ammonium sulfate, ammonium chloride, and ammonium nitrate; and inorganic flocculants such as divalent or higher metal complexes. It is also possible to add an acid to lower H and cause soft flocculation; for example, sulfuric acid or nitric acid can be used.
[0095] The coagulant may be added in the form of either a dry powder or an aqueous solution dissolved in an aqueous medium, but in order to cause uniform coagulation, it is preferable to add it in the form of an aqueous solution. The addition and mixing of the coagulant is preferably carried out at a temperature equal to or lower than the glass transition temperature or melting point of the resin contained in the mixed liquid. By carrying out mixing under this temperature condition, the coagulation proceeds relatively uniformly. The mixing of the coagulant into the mixed liquid can be carried out using a known mixing device such as a homogenizer or a mixer. The coagulation step is a step of forming aggregates of the toner particle size in an aqueous medium. The volume average particle size of the aggregates produced in the coagulation step is preferably 3 μm to 10 μm. The volume average particle size can be measured using a particle size distribution analyzer (Coulter Multisizer III: manufactured by Coulter) by the Coulter method.
[0096] <Step of Obtaining Dispersion Liquid Containing Toner Particles (Fusion Step)> In the fusion step, the dispersion containing the aggregates obtained in the aggregation step is first subjected to termination of aggregation under stirring in the same manner as in the aggregation step by adding an aggregation terminator such as a base capable of adjusting the pH, a chelating compound, or an inorganic salt compound such as sodium chloride. After the dispersion state of the aggregated particles in the dispersion liquid becomes stable due to the action of the aggregation terminator, the aggregated particles are fused by heating to a temperature equal to or higher than the glass transition temperature or melting point of the binder resin, and the particle size is adjusted to a desired particle size. The 50% particle size (D50) based on volume of the toner particles is preferably 3 μm to 10 μm.
[0097] <Cooling process> If necessary, in the cooling step, the temperature of the dispersion liquid containing the toner particles obtained in the fusion step can be cooled to a temperature lower than at least one of the crystallization temperature and the glass transition temperature of the binder resin. By cooling to a temperature lower than at least one of the crystallization temperature and the glass transition temperature, it is possible to prevent the generation of coarse particles. The specific cooling rate can be 0.1°C / min to 50°C / min.
[0098] <Post-processing process> In the toner manufacturing method, after the cooling step, post-treatment steps such as a washing step, a solid-liquid separation step, and a drying step may be performed. By performing the post-treatment steps, toner particles in a dry state are obtained.
[0099] <External addition process> The obtained toner particles may be used as a toner as they are. In the external addition step, inorganic fine particles are externally added to the toner particles obtained in the drying step, as necessary. Specifically, inorganic fine particles such as silica, and resin fine particles such as vinyl resin, polyester resin, and silicone resin are preferably added by applying a shear force in a dry state.
[0100] In the toner production method, boric acid is preferably present in any one of the following steps (1) to (3). The toner production method preferably includes a step of adding a boric acid source (preferably borax) in at least any one of steps (1) to (3). More preferably, in step (2), the boric acid source (preferably borax) is added to the dispersion during mixing of the dispersion before aggregation. In the following steps (1) to (3), if boric acid is present in the dispersion or aggregates, a crystallization-promoting effect is easily obtained in the final crystallization step.
[0101] (1) A resin particle dispersion liquid having a binder resin containing at least a side-chain crystalline polymer B having a monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms is prepared. ManufacturingA dispersion step of (2) an aggregation step of mixing and aggregating at least the resin fine particle dispersion to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together In the aggregation step, boric acid may be added during the step.
[0102] The boric acid source may be boric acid or a compound that can be converted to boric acid by pH control during toner production. For example, a boric acid source may be added and controlled so that boric acid is contained in the aggregates at least in the step (3).
[0103] The boric acid may be present in the aggregate in an unsubstituted state. The boric acid source is preferably at least one selected from the group consisting of organic boric acid, borate salts, borate esters, etc. When the toner is produced in an aqueous medium, it is preferable to add the borate salt in view of reactivity and production stability. Specifically, the boric acid source more preferably includes at least one selected from the group consisting of sodium tetraborate, borax, ammonium borate, etc., and even more preferably is borax.
[0104] Borax is represented by the decahydrate of sodium tetraborate Na2B4O7, and is converted to boric acid in an acidic aqueous solution, so borax is preferably used when used in an acidic environment in an aqueous medium. It may be added in the form of either a dry powder or an aqueous solution dissolved in an aqueous medium, but it is preferable to add it in the form of an aqueous solution in order to cause uniform aggregation.
[0105] Borax may be added in any of the above steps (1) to (3). Preferably, borax is added and mixed in at least one of steps (1) or (2). More preferably, in step (2), when the dispersion is mixed before flocculation, an aqueous borax solution is added to the dispersion and mixed to make the dispersion acidic. The concentration of the aqueous solution may be appropriately changed depending on the concentration to be contained in the toner, and is, for example, 1 to 20% by mass. In order to convert it to boric acid, it is preferable to make the pH acidic before, during, or after the mixing. For example, it may be controlled to 1.5 to 5.0, preferably 2.0 to 4.0.
[0106] Next, the measurement methods for each physical property will be described. <Method for measuring the content of monomer units derived from various polymerizable monomers in polymer B> The content ratio of monomer units derived from various polymerizable monomers in polymer B was measured by: 1 H-NMR was performed under the following conditions. ·Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times: 64 ·Measurement temperature: 30℃ Sample: Place 50 mg of the sample to be measured in a sample tube with an inner diameter of 5 mm, add deuterated chloroform (CDCl3) as a solvent, and dissolve this in a constant temperature bath at 40°C.
[0107] Obtained 1 From the H-NMR chart, a peak that is independent of peaks that are attributable to the components of the monomer unit A and other monomer unit components is selected, and the integral value S1 of this peak is calculated. Similarly, from the peaks attributable to the components of the monomer unit C, a peak independent of the peaks attributable to the components of other monomer units is selected, and the integral value S2 of this peak is calculated. Furthermore, when the polymerizable monomer D is present, a peak independent of the peaks attributable to the components of the monomer unit other than the monomer unit D is selected from the peaks attributable to the components of the monomer unit D, and the integrated value S3 of this peak is calculated.
[0108] The content ratio of the monomer unit A is determined as follows using the above integrated values S1, S2, and S3. Here, n1, n2, and n3 are the numbers of hydrogens in the components to which the peaks focused on for each site are attributed. Content ratio of monomer unit A (mol%) = {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100 Similarly, the content ratios of the monomer unit C and the monomer unit D are determined as follows. Content ratio of monomer unit C (mol%) = {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100 Content ratio of monomer unit D (mol%) = {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100 In the case of the polymer B, when a polymerizable monomer in which the components other than the vinyl group do not contain hydrogen atoms is used, 13 using C-NMR, the measured nuclear is 13 C, and the measurement is performed in single pulse mode, 1 and it is calculated in the same manner by H-NMR. Also, when the toner particles are produced by the suspension polymerization method, the peaks of the release agent and other resins may overlap, and independent peaks may not be observed. As a result, there may be cases where the content ratios of the monomer units derived from various polymerizable monomers in the polymer B cannot be calculated. In that case, a similar suspension polymerization is performed without using the release agent and other resins to produce the polymer B', and the polymer B' can be regarded as the polymer B and analyzed.
[0109] <Calculation method of SP value> SP 12 、SP22 The SP values such as these are calculated according to the calculation method proposed by Fedors as follows: For each polymerizable monomer, the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm) for the atom or atomic group in the molecular structure are calculated from the table in "Polym. Eng. Sci., 14(2), 147-154 (1974)". 3 / mol), (4.184×ΣΔei / ΣΔvi) 0.5 SP value (J / cm 3 ) 0.5 Let us assume that. On the other hand, S.P. 11 , S.P. 21 is calculated in the same manner as above for an atom or atomic group in the molecular structure in a state in which the double bond of the polymerizable monomer is cleaved by polymerization.
[0110] <Identification and Quantitative Analysis of Boric Acid in Toner> The boric acid contained in the toner is identified and the content thereof is measured by the following method. Whether or not a toner contains boric acid can be confirmed by using infrared absorption spectroscopy. Specifically, an appropriate amount of toner or toner particle sample resin is mixed with potassium bromide (KBr) and molded. This is used to measure the infrared absorption spectrum. Boric acid has a vibration frequency of 1380 cm -1 Since there is an absorption wavelength in this portion, it is possible to confirm the presence of boric acid. In addition, elemental analysis can be performed by energy dispersive X-ray spectroscopy (EDX) using a transmission electron microscope (TEM) to confirm whether boron derived from boric acid is present in the observed portion of the cross section.
[0111] The amount of boric acid contained in the toner is measured using fluorescent X-rays and a calibration curve method is used. To obtain the measurement value, an aluminum ring (inner diameter 40 mm, outer diameter 43 mm, height 5 mm) is placed on the die for sample molding of a semi-automatic MiniPress machine (Specac). 3 g of toner is placed in the ring and pressurized for 1 minute at a pressure of 15 t to produce a pellet for measurement. A pellet molded to a thickness of about 3 mm and a diameter of about 40 mm is used. Measurements are performed under the following conditions using a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds. In the case of boron, detection is performed using a proportional counter (PC). The acceleration voltage and current of the X-ray generator are set to 32 kV and 125 mA, respectively. Measurements are performed under the above conditions, boron is identified based on the peak position of the obtained X-rays, and the counting rate (unit: cps), which is the number of X-ray photons per unit time, is measured. In addition, the amount of boric acid (mass%) in the toner is calculated from a separately prepared calibration curve for boric acid.
[0112] If necessary, in order to eliminate the influence of external additives, the measurement can be performed using toner particles from which external additives have been removed by the following method. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. In a centrifuge tube (50 mL capacity), add 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of nonionic surfactants, anionic surfactants, and organic builders, manufactured by Wako Pure Chemical Industries, Ltd.). Add 1.0 g of toner to this and break up the toner clumps with a spatula or the like. Shake the centrifuge tube at 300 strokes per minute (spm) for 20 minutes in a shaker (AS-1N, sold by AS ONE Corporation). After shaking, transfer the solution to a glass tube for a swing rotor (50 mL) and separate it in a centrifuge (H-9R, manufactured by Kokusan Corporation) at 3,500 rpm for 30 minutes. This operation separates the toner particles from the external additives. Visually check that the toner particles and the aqueous solution are sufficiently separated, and collect the toner particles that have separated to the top layer with a spatula or similar. The collected toner particles are filtered through a vacuum filter, and then dried in a dryer for at least one hour to obtain a sample for measurement. This operation is carried out multiple times to ensure the required amount.
[0113] <Method of measuring weight average molecular weight (Mw) and number average molecular weight (Mn) of polymer B and amorphous resin> The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer B and the tetrahydrofuran (THF) soluble portion of the amorphous resin are measured by gel permeation chromatography (GPC) as follows. First, the sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: 7 columns of Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko Co., Ltd.) Eluent: Tetrahydrofuran (THF) ·Flow rate: 1.0mL / min Oven temperature: 40.0℃ Sample injection volume: 0.10mL In calculating the molecular weight of the sample, standard polystyrene resins (product names: TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F- A molecular weight calibration curve prepared using "A-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" (manufactured by Tosoh Corporation) is used.
[0114] <Acid value measurement method> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of a resin such as polymer B is measured in accordance with JIS K 0070-1992, and specifically, is measured according to the following procedure. (1) Preparation of reagents
[0115] Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution. Dissolve 7 g of special grade potassium hydroxide in 5 mL of water, and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is determined by placing 25 mL of 0.1 mol / L hydrochloric acid in an Erlenmeyer flask, adding several drops of the phenolphthalein solution, and titrating with the potassium hydroxide solution, from the amount of potassium hydroxide solution required for neutralization. The 0.1 mol / L hydrochloric acid used is prepared in accordance with JIS K 8001-1998. (2) Operation (A) Main Test 2.0 g of the crushed polymer B sample is precisely weighed into a 200 mL Erlenmeyer flask, 100 mL of a toluene / ethanol (2:1) mixed solution is added, and the mixture is dissolved over 5 hours. Then, several drops of the phenolphthalein solution are added as an indicator, and the mixture is titrated with the potassium hydroxide solution. The end point of the titration is when the light red color of the indicator continues for 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used). (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (ml), C is the amount of potassium hydroxide solution added for the main test (mL), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).
[0116] <Measuring method of toner melting point and half-value width> The melting point and half-value width of the crystalline peak corresponding to the side-chain crystalline polymer B of the toner are measured under the following conditions using a DSC Q1000 (manufactured by TA Instruments). Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃ The melting points of indium and zinc are used to correct the temperature of the detector, and the heat of fusion of indium is used to correct the amount of heat. Specifically, 5 mg of the sample is weighed out and placed in an aluminum pan, and differential scanning calorimetry is performed. An empty silver pan is used as a reference. The peak temperature of the maximum endothermic peak in the first heating process is taken as the melting point (°C). The half-width is a value automatically calculated by the analysis software. Here, the half-width is also called the full width at half maximum. If there are multiple peaks, the peak with the maximum amount of endothermic heat is used to determine whether or not the peak corresponds to polymer B is determined by comparing it with the peak measured for polymer B separated from the toner, or a sample prepared from polymer B with a known composition.
[0117] <Method for measuring the glass transition temperature Tg of amorphous resin> The glass transition temperature Tg was measured using a differential scanning calorimeter "Q2000" (TA Instrument Measurements are performed using a 3000K ... During the temperature rise process, a specific heat change is obtained in the temperature range of 40° C. to 100° C. The intersection point between the line midway between the baselines before and after the specific heat change occurs and the differential thermal curve is defined as the glass transition temperature of the resin.
[0118] <Measurement of toner particle size> The particle size of the toner particles can be measured by the pore electrical resistance method. For example, it can be measured and calculated using the "Coulter Counter Multisizer 3" and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.). A precision particle size distribution measuring device using the pore electrical resistance method (product name: Coulter Counter Multisizer 3) and dedicated software (product name: Beckman Coulter Multisizer 3 Version 3.51, manufactured by Beckman Coulter, Inc.) are used. The aperture diameter is 100 μm, and measurements are made with an effective number of measurement channels of 25,000. The measurement data is then analyzed and calculated.
[0119] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example ISOTON manufactured by Beckman Coulter. II (trade name) can be used. Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using (standard particle 10.0 μm, manufactured by Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. Also, set the current to 1600 μA, the gain to 2, and the electrolyte to ISOTON II (trade name), and perform the measurement. Check the aperture tube flush after setting. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0120] The specific measurement method is as follows. (1) Place the electrolytic solution in a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3. Pour in approximately 200 mL of liquid, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) About 30 mL of the aqueous electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and about 0.3 mL of a diluted solution of Contaminon N (trade name) (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments, manufactured by Wako Pure Chemical Industries, Ltd.) diluted three times by mass with ion-exchanged water is added thereto. (3) An ultrasonic disperser (product name: Ultrasonic Dispersion) with two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. A predetermined amount of ion-exchanged water and approximately 2 mL of Contaminon N (trade name) are added to the water tank of a chromatograph (System Tetora 150, manufactured by Nikkaki Bios Co., Ltd.). (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) In a state where the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. Note that during ultrasonic dispersion, the water temperature of the water tank is set to 10°C or higher and 40°C or lower. Adjust appropriately so that the temperature remains below ℃. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1). EXAMPLES
[0121] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following formulations, "parts" are by weight unless otherwise specified.
[0122] <Preparation of Side Chain Crystalline Polymer B1> The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. Toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, methacrylonitrile, and styrene in the ratio shown below.) (Behenyl acrylate (polymerizable monomer A) 67.0 parts (28.9 mol%)) (Methacrylonitrile (polymerizable monomer C) 22.0 parts (53.8 mol%)) (Styrene (polymerizable monomer D) 11.0 parts (17.3 mol %)) t-Butyl peroxypivalate 0.5 parts (Polymerization initiator, NOF Corp.: Perbutyl PV) The inside of the reaction vessel was heated to 70°C while stirring at 200 rpm, and polymerization reaction was carried out for 12 hours, to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Subsequently, the solution was cooled to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring, to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain a side chain crystalline polymer B1. The weight average molecular weight (Mw) of the side chain crystalline polymer B1 was 68,900, the acid value was 0.0 mgKOH / g, and the melting point was 63°C.
[0123] The polymer B1 was analyzed by NMR and found to contain 28.9 mol % of monomer units derived from behenyl acrylate, 53.8 mol % of monomer units derived from methacrylonitrile, and 17.3 mol % of monomer units derived from styrene. The SP values of the monomer units were also calculated.
[0124] <Production Examples of Side Chain Crystalline Polymers B2 to B15> Side chain crystalline polymers B2 to B15 were obtained by carrying out the reaction in the same manner as in the production example of side chain crystalline polymer B1, except that the polymerizable monomers and the parts thereof were changed as shown in Table 1. The physical properties of side chain crystalline polymers B1 to B15 are shown in Table 2. The SP values of the polymerizable monomers and monomer units used in the production examples are shown in Table 3.
[0125] <Preparation of Amorphous Resin 1 Other than Side Chain Crystalline Polymer B> The following raw materials were charged into a heated and dried two-neck flask while introducing nitrogen. Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane 30.0 copies Polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane 33.0 copies Terephthalic acid 21.0 parts Dodecenyl succinic acid 15.0 parts Dibutyltin oxide 0.1 parts After the system was purged with nitrogen by reducing the pressure, stirring was carried out at 215°C for 5 hours. The temperature was then gradually raised to 230°C under reduced pressure while continuing to stir, and maintained at that temperature for a further 2 hours. When the mixture became viscous, it was air-cooled to terminate the reaction, synthesizing amorphous resin 1, an amorphous polyester. The number average molecular weight (Mn) of amorphous resin 1 was 5,200, and the weight average molecular weight The molecular weight (Mw) was 23,000 and the glass transition temperature (Tg) was 55°C.
[0126] <Preparation of Amorphous Resin 2 Other than Side Chain Crystalline Polymer B> Solvent: Xylene 100.0 parts Styrene 95.0 parts n-Butyl acrylate 5.0 parts Polymerization initiator: 0.3 parts t-butyl peroxypivalate (NOF Corp.: Perbutyl PV) The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 185°C while stirring at 200 rpm to carry out a polymerization reaction for 10 hours. The solvent was then removed and the mixture was vacuum dried at 40°C for 24 hours to obtain styrene acrylic amorphous resin 2. The weight average molecular weight Mw of amorphous resin 2 was 35,000, the glass transition temperature Tg was 58°C, and the acid value was 0.0 mgKOH / g.
[0127] <Production Example of Polymer Microparticle Dispersion 1> Toluene (Wako Pure Chemical Industries): 300 parts Side chain crystalline polymer B-1: 100 parts The above materials were weighed, mixed, and dissolved at 90° C. Separately, 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700 parts of ion-exchanged water and dissolved by heating at 90° C. The toluene solution and the aqueous solution were then mixed and stirred at 7000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix).Furthermore, the mixture was emulsified at a pressure of 200 MPa using a high pressure impact dispersing device Nanomizer (manufactured by Yoshida Kikai Kogyo).After that, the toluene was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion (polymer microparticle 1 dispersion) with a concentration of polymer microparticle 1 of 20 mass%. The volume-based 50% particle size (D50) of the polymer microparticles 1 was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.40 μm.
[0128] <Production Examples of Polymer Microparticle Dispersions 2 to 18> In the preparation example of the polymer microparticle 1 dispersion, emulsification was carried out in the same manner as above, except that the side chain crystalline polymer and the amorphous resin were changed as shown in Table 4, to obtain polymer microparticle 2 to 18 dispersions. The physical properties of the polymer microparticle 1 to 18 dispersions are shown in Table 4.
[0129] <Production Examples of Polymer Microparticle 19 Dispersion and Polymer Microparticle 20 Dispersion> Tetrahydrofuran (Wako Pure Chemical Industries): 300 parts Amorphous resin 1: 100 parts Anionic surfactant Neogen RK (Daiichi Kogyo Seiyaku): 0.5 parts The above materials were weighed, mixed, and dissolved. Next, 20.0 parts of 1 mol / L ammonia water was added, and the mixture was stirred at 4000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). Furthermore, 700 parts of ion-exchanged water was added at a rate of 8 g / min to precipitate fine particles of amorphous resin 1. Thereafter, tetrahydrofuran was removed using an evaporator, and the concentration was adjusted with ion-exchanged water, resulting in an aqueous solution with a concentration of fine particles of amorphous resin 1 of 20% by mass. A system dispersion (polymer fine particle 19 dispersion) was obtained. The volume-based 50% particle diameter (D50) of the polymer fine particle 19 dispersion was 0.13 μm. As for the polymer fine particle 20 dispersion, the same procedure as in the preparation example of the polymer fine particle 19 dispersion was followed except that the amorphous resin 1 was changed to the amorphous resin 2 to obtain the polymer fine particle 20 dispersion.
[0130] <Production Example of Release Agent Microparticle Dispersion> Release agent HNP-51 (manufactured by Nippon Seiro) 100 parts Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 5 parts 395 parts of ion-exchanged water The above materials were weighed and placed in a mixing vessel equipped with a stirrer, then heated to 90°C and circulated through a Clearmix W Motion (M Technique) for 60 minutes for dispersion treatment. The dispersion treatment conditions were as follows: Rotor outer diameter: 3cm Clearance: 0.3mm Rotor speed: 19000 r / min Screen rotation speed: 19000 r / min After the dispersion treatment, the mixture was cooled to 40°C under cooling treatment conditions of a rotor rotation speed of 1000 r / min, a screen rotation speed of 0 r / min, and a cooling rate of 10°C / min, thereby obtaining an aqueous dispersion (release agent fine particle dispersion) with a release agent fine particle concentration of 20 mass%. The 50% particle size (D50) on a volume basis of the release agent (aliphatic hydrocarbon compound) fine particles was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm.
[0131] <Production of colorant particle dispersion> Coloring agent 50.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 7.5 parts Ion-exchanged water 442.5 parts The above materials were weighed, mixed, dissolved, and dispersed for approximately 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to obtain an aqueous dispersion (colorant particle dispersion) containing dispersed colorant particles with a concentration of 10% by mass. The volume-based 50% particle size (D50) of the colorant fine particles was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm.
[0132] <Preparation of Silica Microparticles 1> Fumed silica (product name: AEROSIL380S, specific surface area by BET method: 380 m 2 / g, number average particle diameter of primary particles 7 nm, manufactured by Nippon Aerosil Co., Ltd.) to 10.0 parts of polydimethylsiloxane (viscosity = 100 mm 2 / s) was sprayed into the mixture, and stirring was continued for 30 minutes. Thereafter, the temperature was raised to 300° C. with stirring, and stirring was continued for another 2 hours to prepare silica microparticles 1.
[0133] <Toner 1 Manufacturing Example> [Toner production by emulsion aggregation method] ·Polymer fine particles 1 dispersion 500.0 parts Release agent fine particle dispersion 50.0 parts Colorant fine particle dispersion 80.0 parts Ion-exchanged water 160.0 parts ·10.0% by mass borax aqueous solution 19.0 parts (Borax; Sodium tetraborate decahydrate Na2B4O7·10H2O, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) The above materials were put into a round stainless steel flask and mixed. Then, a homogenizer Ultra Turrax T50 (IKA) was used to disperse the mixture at 5000 r / min for 10 minutes. After adding a 1.0% aqueous nitric acid solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The volume average particle size of the formed aggregated particles was appropriately confirmed using a Coulter Multisizer III, and when aggregated particles of 6.0 μm were formed, the pH was adjusted to 9.0 using a 5% aqueous sodium hydroxide solution. Then, the mixture was heated to 75°C while continuing to stir. The aggregated particles were fused by holding at 75°C for 1 hour. The mixture was then cooled to 50°C and held there for 3 hours to promote crystallization of the polymer. It was then cooled to 25°C, filtered, and separated into solid and liquid, and then washed with ion-exchanged water. After washing, the mixture was dried using a vacuum dryer to obtain toner particles 1 with a weight average particle size (D4) of 6.07 μm.
[0134] External addition was performed on the above toner particles 1. 100.0 parts of toner particles 1 and 1.8 parts of silica fine particles 1 were dry mixed for 5 minutes using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) to obtain toner 1. The physical properties of the obtained toner 1 are shown in Table 5.
[0135] <Production examples of toners 2-22 and 27-30> [Toner production by emulsion aggregation method] Toners 2 to 22 and 27 to 30 were obtained in the same manner as in Production Example 1 of Toner 1, except that the type of polymer fine particle dispersion and the concentration and amount of borax aqueous solution were changed as shown in Table 5. The toner physical properties are shown in Table 5.
[0136] <Production Example of Toner 23> [Toner production by emulsion aggregation method] ·Polymer fine particle 2 dispersion liquid 350.0 parts Release agent dispersion 50.0 parts Colorant dispersion 80.0 parts Ion-exchanged water 160.0 parts The above materials were put into a round stainless steel flask and mixed. Then, the mixture was dispersed at 5000 r / min for 10 minutes using a homogenizer Ultra Turrax T50 (manufactured by IKA). After adding a 1.0% nitric acid aqueous solution and adjusting the pH to 3.0, the mixture was heated to 58°C using a stirring blade in a heating water bath while appropriately adjusting the rotation speed so that the mixture was stirred. The volume average particle size of the formed aggregated particles was appropriately confirmed using a Coulter Multisizer III, and when aggregated particles of 4.0 μm were formed, 19.0 parts of a 10.0 mass% borax aqueous solution was added. After adding the borax aqueous solution, 150.0 parts of the polymer microparticle 2 dispersion were added, and the volume average particle size of the aggregated particles was confirmed again. When aggregated particles of 6.0 μm were formed, the pH was adjusted to 9.0 using a 5% sodium hydroxide aqueous solution. Then, the mixture was heated to 75°C while continuing to stir. The aggregated particles were fused by holding at 75°C for 1 hour. The mixture was then cooled to 50°C and held there for 3 hours to promote crystallization of the polymer. The mixture was then cooled to 25°C, filtered, and separated into solid and liquid form, and then washed with ion-exchanged water. After washing, the mixture was dried using a vacuum dryer to obtain toner particles 23 having a weight average particle size (D4) of 6.21 μm. The same external additions as in Toner 1 were made to Toner Particles 23 to obtain Toner 23. The physical properties of Toner 23 are shown in Table 5.
[0137] <Toner 24 Manufacturing Example> In the production example of toner 1, 19.0 parts of a 10.0% by mass borax aqueous solution was mixed with 12.0 parts of a 10.0% by mass boric acid aqueous solution (boric acid; boric acid H3BO3 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). Toner 24 was obtained in the same manner as in the production example of toner 1, except that the amount of the toner used was changed to 1 part. The physical properties of toner 24 are shown in Table 5.
[0138] <Toner 25 Manufacturing Example> [Toner production by suspension polymerization method] Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, methacrylonitrile, and styrene in the ratio shown below.) (Behenyl acrylate (polymerizable monomer A) 60.0 parts (28.5 mol%)) (Methyl methacrylate (polymerizable monomer C) 29.0 parts (52.4 mol%)) (Styrene (polymerizable monomer D) 11.0 parts (19.1 mol%)) Pigment Blue 15:3 6.5 parts Di-t-butyl aluminum salicylate 1.0 parts Release agent 10.0 parts (Release agent: Nippon Seiro Co., Ltd.: HNP-51, melting point: 74°C) Toluene 100.0 parts ·10.0% by mass borax aqueous solution 36.8 parts A mixture of the above materials was prepared. The mixture was placed in an attritor (manufactured by Nippon Coke Corporation) and dispersed at 200 rpm for 2 hours using zirconia beads with a diameter of 5 mm to obtain a raw material dispersion. On the other hand, 735.0 parts of ion-exchanged water and 16.0 parts of trisodium phosphate (12-hydrate) were added to a container equipped with a high-speed stirring device homomixer (manufactured by Primix Corporation) and a thermometer, and the temperature was raised to 60°C while stirring at 12000 rpm. An aqueous calcium chloride solution in which 9.0 parts of calcium chloride (2-hydrate) was dissolved in 65.0 parts of ion-exchanged water was added thereto, and the mixture was stirred at 12000 rpm for 30 minutes while maintaining the temperature at 60°C. 10% hydrochloric acid was added thereto to adjust the pH to 6.0, and an aqueous medium containing a dispersion stabilizer was obtained. Next, the raw material dispersion liquid was transferred to a container equipped with a stirrer and a thermometer, and heated to 60° C. while stirring at 100 rpm. 8.0 parts of t-butyl peroxypivalate (Perbutyl PV, manufactured by NOF Corp.) was added as a polymerization initiator, and the mixture was stirred at 100 rpm for 5 minutes while maintaining the temperature at 60° C., and then poured into the aqueous medium being stirred at 12000 rpm with the high-speed stirrer. Stirring was continued for 20 minutes at 12000 rpm with the high-speed stirrer while maintaining the temperature at 60° C., to obtain a granulation liquid.
[0139] The granulation liquid was transferred to a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube, and heated to 70° C. while stirring at 150 rpm under a nitrogen atmosphere. A polymerization reaction was carried out at 150 rpm for 10 hours while maintaining the temperature at 70° C. Thereafter, the reflux condenser was removed from the reaction vessel, and the reaction liquid was heated to 95° C., and then stirred at 150 rpm for 5 hours while maintaining the temperature at 95° C. to remove toluene, thereby obtaining a toner particle dispersion liquid. The resulting toner particle dispersion was cooled to 20°C while stirring at 150 rpm, and then diluted hydrochloric acid was added while maintaining stirring until the pH reached 1.5 to dissolve the dispersion stabilizer. The solid content was filtered off, thoroughly washed with ion-exchanged water, and then vacuum-dried at 40°C for 24 hours to obtain toner particles 25 containing the side-chain crystalline polymer B-16 of the monomer composition.
[0140] Further, a side chain crystalline polymer B-16' was obtained in the same manner as in the above-mentioned toner particle 25, except that pigment blue 15:3, aluminum di-t-butyl salicylate, and a release agent were not used. The weight average molecular weight (Mw) of the polymer B-16' was 56,800, the acid value was 0.0 mgKOH / g, and the melting point was 55°C. When the polymer A1 was analyzed by NMR, it was found to contain 28.5 mol% of monomer units derived from behenyl acrylate, 52.4 mol% of monomer units derived from methyl methacrylate, and 19.1 mol% of monomer units derived from styrene. The above-mentioned polymer B-16 and polymer B-16' were obtained in the same manner. Since they were manufactured using the same method, it was determined that they had equivalent physical properties. The same external additions as in Toner 1 were made to Toner Particles 25 to obtain Toner 25. The physical properties of Toner 25 are shown in Table 5.
[0141] <Toner 26 Manufacturing Example> [Toner production by pulverization method] Side chain crystalline polymer B2 100.0 parts CI Pigment Blue 15:3 6.5 parts Release agent 12.0 parts (Nippon Seiro Co., Ltd.: HNP-51, melting point: 74℃) Charge control agent (T-77: manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts Boric acid powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 1.5 parts The above materials were premixed in an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.), and then melt-kneaded using a twin-screw kneading extruder (Model PCM-30 manufactured by Ikegai Iron Works Co., Ltd.). The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then pulverized with a mechanical pulverizer (T-250 manufactured by Turbo Kogyo Co., Ltd.). The obtained finely pulverized powder was classified with a multi-division classifier utilizing the Coanda effect to obtain toner particles 26 having a weight average particle size (D4) of 7.00 μm. The same external additions as in Toner 1 were made to Toner Particles 26 to obtain Toner 26. The physical properties of Toner 26 are shown in Table 5.
[0142] <Example 1> Toner 1 was subjected to the following evaluations. <1> Evaluation of low temperature fixability The process cartridge filled with toner was left in a normal temperature and humidity (N / N) environment (23°C, 60% RH) for 48 hours. Using an LBP-7700C modified to operate even without the fixing unit, an unfixed image was printed with an image pattern in which 9 10mm x 10mm square images were evenly arranged on the entire transfer paper. The amount of toner on the transfer paper was 0.80mg / cm. 2 The transfer paper was Fox River Bond (90 g / m 2 ) was used. The fixing unit was an external fixing unit that had been removed from the LBP-7700C and was designed to operate outside the laser beam printer. The fixing temperature of the external fixing unit was raised in 10°C increments from 100°C, and fixing was performed at a process speed of 240mm / sec. Fixing image at 50g / cm 2 The sample was rubbed with Silbon paper (Lenz Cleaning Paper "dasper(R)" (Ozu Paper Co. Ltd.)) under a load of 1000 g. The temperature at which the density loss rate before and after rubbing became 20% or less was defined as the fixing start temperature, and the low-temperature fixing property was evaluated according to the following criteria. The evaluation results are shown in Table 6. [Evaluation Criteria] A: Fixing start temperature is 100℃ B: Fixing start temperature is 110℃ C: Fixing start temperature is 120℃ D: Fixing start temperature is 130°C or higher
[0143] <2> Evaluation of heat resistance and preservation 10 g of toner was weighed into a 50 mL plastic cup and left in a thermostatic chamber at 52.5° C. for 5 days. After leaving the toner, the toner was visually observed and the heat resistance storage stability (blocking property) was evaluated according to the following criteria. C or higher was judged to be good. The results are shown in Table 6. A: Just turn the cup and it will loosen up quickly. B: There are lumps, but they get smaller and break apart as you turn the cup. C: Even after rotating the cup to loosen the contents, lumps remain. D: There are large lumps that do not break apart even when you turn the cup.
[0144] <3> durability A commercially available Canon printer LBP9200C was used to evaluate durability. The LBP9200C uses one-component contact development, and a toner regulating member regulates the amount of toner on the developer carrier. The cartridge for evaluation was a commercially available cartridge in which the toner was removed, the inside was cleaned with an air blower, and then filled with 260 g of the toner to be evaluated. The above cartridge was installed in the cyan station, and dummy cartridges were installed in the other stations to perform the evaluation. At 23℃ and 50% RH, Fox River Bond (90g / m 2 ) was used to print 20,000 images with a print rate of 1%. After that, the toner loading was 0.3 mg / cm 2 A halftone image was output, and the presence or absence of vertical streaks caused by toner melting to the regulating member, so-called development streaks, was confirmed on the developer carrier and on the halftone image. The evaluation criteria are as follows. C or higher was judged to be good. The results are shown in Table 6. A: No streaks on the developer carrier. B: Streaks are observed on the developer carrier but not on the halftone image. C: Minor streaks are observed on the halftone image. D: Clear streaks on halftone image.
[0145] <Examples 2 to 26> Toners 2 to 26 were evaluated in the same manner as in Example 1. The results are shown in Table 6.
[0146] <Comparative Examples 1 to 4> Toners 26 to 30 were evaluated in the same manner as in Example 1. The results are shown in Table 6.
[0147] [Table 1]
[0148] [Table 2]
[0149] [Table 3]
[0150] [Table 4]
[0151] [Table 5] In the table, the unit of the half width is ° C., and the unit of the weight average particle size (D4) is μm.
[0152] [Table 6]
Claims
1. A toner having toner particles containing a binder resin, the binder resin comprises a side-chain crystalline polymer B having a monomer unit A formed of at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms; The toner particles contain boric acid.
2. 2. The toner according to claim 1, wherein the content of the side chain crystalline polymer B in the binder resin is 50.0% by mass or more.
3. 3. The toner according to claim 1, wherein the side chain crystalline polymer B comprises the monomer unit A formed from the polymerizable monomer A and a monomer unit C formed from a polymerizable monomer C different from the polymerizable monomer A.
4. The SP value of the monomer unit A in the side chain crystalline polymer B is 11 (J / cm 3 ) 0.5 The SP value of the monomer unit C is SP 21 (J / cm 3 ) 0.5 year, The SP value of the polymerizable monomer A is 12 (J / cm 3 ) 0.5 The SP value of the polymerizable monomer C is SP 22 (J / cm 3 ) 0.5 4. The toner according to claim 3, which satisfies the following formulae (1) and (2): 2.00≦(SP 21 2017 11 )≦25.00 ・・・(1) 0.50≦(SP 22 2017 12 )≦15.00 ・・・(2)
5. 5. The toner according to claim 3, wherein the polymerizable monomer C is at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and methyl methacrylate.
6. the content ratio of the monomer unit A in the side chain crystalline polymer B is 35.0% by mass to 80.0% by mass, 6. The toner according to claim 3, wherein a content ratio of said monomer unit C in said side chain crystalline polymer B is 15.0% by mass to 55.0% by mass.
7. The side chain crystalline polymer B is a polymerizable monomer different from the polymerizable monomer A and the polymerizable monomer C. having a monomer unit D formed by a synthetic monomer D, 7. The toner according to claim 3, wherein the polymerizable monomer D is styrene.
8. 8. The toner according to claim 1, wherein the content of the boric acid in the toner is from 0.1% by mass to 10.0% by mass.
9. 9. The toner according to claim 1, wherein the half-value width of the peak corresponding to the side-chain crystalline polymer B measured by a differential scanning calorimeter of the toner is 2.00° C. or less.
10. A method for producing a toner having toner particles containing a binder resin, comprising the steps of: The method for producing the toner comprises the following steps (1) to (3): (1) a dispersing step of preparing a dispersion of resin fine particles having the binder resin, the binder resin including at least a side-chain crystalline polymer B having a monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms; (2) an aggregation step of mixing at least the dispersion of the resin fine particles and aggregating the mixture to form aggregates; and (3) A fusion step of heating the aggregates to fuse them together having The toner production method is characterized in that boric acid is present in the dispersion liquid in at least any one of the steps (1) to (3).
11. A method for producing a toner having toner particles containing a binder resin, comprising the steps of: The method for producing the toner comprises the following steps (1) to (3): (1) a dispersing step of preparing a dispersion of resin fine particles having the binder resin, the binder resin including at least a side-chain crystalline polymer B having a monomer unit A derived from at least one polymerizable monomer A selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms; (2) an aggregation step of mixing at least the dispersion of the resin fine particles and aggregating the mixture to form aggregates; and (3) A fusion step of heating the aggregates to fuse them together having The toner production method is characterized in that borax is added to the dispersion liquid in at least any one of the steps (1) to (3).
12. 12. The method for producing a toner according to claim 10, further comprising the step of adding an aqueous borax solution to the dispersion liquid during mixing of the dispersion liquid in the step (2), and mixing the dispersion liquid to make the dispersion liquid acidic.
Citation Information
Patent Citations
Electrophotographic toner
JP1996202072A
Method of manufacturing electrophotographic developer
JP2001228650A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge and image formation apparatus
JP2012042539A
Image forming method
JP2013020113A
Toner
JP2014130243A